Nas sombras da família coelho: a dinâmica de uma dominação política - Santos, Ruyter Antônio Bezerra dos (2013)
As one of the most important cities in the state of Pernambuco, Petrolina is settled in the Pernabucanian backwoods, a place that still holds its own traditions and manners. Petrolina s economy is mainly based on primary activities. It s politics is run by Family groups which preserve themselves and remain in power, using the clientelism, which could be said as a give and get practice. That means that the suffrage is a currency to exchange benefits. The present study analyses facts occurred in the political history of the Coelho s Family, which still dominates the local Politics. They persist as heirs of the old system of Coronelism that is maintaining their power structuring a political machine, which is able to make them unbeatable for over fifty years. Despite of a family internal division, it benefits all of them, directly or indirectly. Based on empirical observation, we set a brief historical of the Coelho s family facts, in order to demonstrate the range of their power through the ancestry, which is to say we ve described the local political labyrinths. Our metodological choices were driven by the comprehensive sociology, through the Weberian ideal types, in order to find the answers for the historical, social and political conformation of the facts, in consonance with the reality. According to that, we ve studied the Coelho s political trajectory from 1968 to 2012, considering the election periods. Commonplace: where a new generation becomes active subjects on a new apprenticeship, moral and intellectual. After all, they are all family heirs